Both Myosin-10 Isoforms Are Required for Radial Neuronal Migration in the Developing Cerebral Cortex. (7th January 2013) - Ju, Xing-Da; Guo, Ye; Wang, Nan-Nan; Huang, Ying; Lai, Ming-Ming; Zhai, Yan-Hua; Guo, Yu-Guang; Zhang, Jian-Hua; Cao, Rang-Juan; Yu, Hua-Li; Cui, Lei; Li, Yu-Ting; et al.
Abstract : During embryonic development of the mammalian cerebral cortex, postmitotic cortical neurons migrate radially from the ventricular zone to the cortical plate. Proper migration involves the correct orientation of migrating neurons and the transition from a multipolar to a mature bipolar morphology. Herein, we report that the 2 isoforms of Myosin-10 (Myo10) play distinct roles in the regulation of radial migration in the mouse cortex. We show that the full-length Myo10 (fMyo10) isoform is located in deeper layers of the cortex and is involved in establishing proper migration orientation. We also demonstrate that fMyo10-dependent orientation of radial migration is mediated at least in part by the netrin-1 receptor deleted in colorectal cancer. Moreover, we show that the headless Myo10 (hMyo10) isoform is required for the transition from multipolar to bipolar morphologies in the intermediate zone. Our study reveals divergent functions for the 2 Myo10 isoforms in controlling both the direction of migration and neuronal morphogenesis during radial cortical neuronal migration.